Periprocedural Pericardial Effusion Complicating Transcatheter Left Atrial Appendage Occlusion: A Report From the NCDR LAAO Registry - Matthew J. Price; Miguel Valderrábano; Sarah Zimmerman; Daniel J. Friedman; Saibal Kar; Jeptha P. Curtis; Frederick A. Masoudi; James V. Freeman (2022)
Pericardial effusion (PE) is a potential complication of transcatheter left atrial appendage occlusion. The objective of this study was to investigate the incidence, associated characteristics, and outcomes of PE following left atrial appendage occlusion.